The unsettlers : in search of the good life in today's America - Sundeen, Mark, 1970- (Riverhead Books, 2017)
A work of immersive journalism steeped in a distinctively American social history and sparked by a personal quest, The Unsettlers traces the search for the simple life through the stories of three families of new pioneers and what inspired each of them to look for--or create--a better existence. Captivating and clear-eyed, it dares us to imagine what a sustainable, ethical, authentic future might actually look like.--